Kajian Pengembangan Konsep Waterfront City di Kawasan Pesisir Kota Ambon - Notanubun, Rivai; Mussadun, Mussadun (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Various activities that exist in this area utilized by the local government as the starting point of planning Ambon Waterfront City. This research aims to study the development concept of Waterfront City in the coastal area of Ambon City. This research approach using qualitative methods that used the method of purposive sampling and snowball techniques. The analysis process used a triangulation technique. The research results showed that the coastal area of Sirimau District, from physical environment aspect, show the characteristic of hilly topography and mountainsides. The problems in the economic’s aspect showed by the system of fishing production, which less optimum in the utilization of fishery products. It caused by less innovation of fish processing and the limitation of infrastructures and facilities, and promotion of this product. Furthermore, the problems of social culture aspect, shown in the disappearance of local identities of coastal communities, disappearance priority of coastal activity, and less public awareness regarding the coastal area management. Based on these results, the coastal area in the City of Ambon did not accord yet with the development plans, theories, and concepts of Waterfront City. Therefore, to fit this area characteristics with the truth Waterfront City concepts, it is important to direct the development of this concept according to the characteristic of the coastal area through to the intervention of programs as follows: a). Rezoning of coastal settlements pursue the regulation of conservation areas along the river and coastal, b). Re-conservation of the damaged coral reef, c). Rehabilitation and coastal zone reclamation as the main trades and services zones corresponding to the service functions that support Waterfront City’s concepts.